PRELIMINARY STUDY OF MICROSTRUCTURE DEPENDENCE OF MAGNETORESISTANCE BEHAVIOR ON Sm.-xLaxMo2Ge2 COMPOUND WITH X=O,l-o,3 - Setyo Purwanto; Wagiyo Wagiyo; M. Danil; Wisnu A.A; Rifai R. Muslich; Yasuo Yamaguchi; H. Yamauchi (ISSN 1410-5594)
AbstractPRELIMINARY STUDY OF MICROSTRUCTURE DEPENDENCE OF MAGNETORESISTANCE BEHAVIORON SmI. ' La , Mn 2G e 2 COMPOUND WITH x=O.l--O.3. We present the microstructure dependence of magnetoresistancebehavior in Sml.,La,Mn2Ge2 compound with x=0.1~0.3. We found that in bulk samples after milling and cold pressingP=10 tonlcm2 the magnetoresistance properties have improved from 0.6% to almost 7% with the adding of La concentration10%,20% and 30%. The bulk samples were prepared by tri arc melting, melted 4-5 times with the Ti addition for oxygen getter.After that, the samples were annealed for 96 hours at 900 °C at the vaccum furnace to make a good homogeneity. X -ray diffractionmeasurement was done using Cu target then the data was refined by Rietan software. Scanning electron micrograph data a pelletsamp.lesw ere taken by SEM 515 from Phillips company with two thousands magnification and operation power 20keV. Fromthe micrograph results, it was shown that the granular diameter increases with the Lanthanum content. In this preliminary studywe can conclude the magnetoresistance behavior is related to the density of samples and also to the fraction of primary phase ofSm La Mn Ge Analysis on this magnetoresistance behavior with magnetic granular solid model can help understanding this I- x x 2 2phenomenon.ABSTRAKSTurn PENDAHULUAN HUBUNGAN ANTARA MIKROSTRUKTUR DENGAN SIFAT MAGNETO RESISTANSIPADA Sml-lLa.Mn"Ge] UNTUKx = O,1-{},3. Pada makalah ini disampaikan basil penelitian awal tentang ketergantungansifat magnetoresistance bahan terhadap strukturmikro pada paduan in Sm1-.La.Mn2Ge2d engan x = 0,1-{),3. Hasil pengukuranpada cuplikan pelet pada tekanan P=10 ton/cm2 memperlihatkan kenaikan sifat magnetoresistance bahandari 0,6 % menjadi 7 %dengan penggantian unsur Sm oleh unsur La pada konsentrasi 10 %, 20 % clan 30 %. Pembuatan cuplikan dilakukan denganmetoda tri arc melting, yang dilakukan sebanyak 4 sampai 5 dengan Ii yang dilebur ter~ebih dahulu sebagai penyerap oksigen.Setelah itu cuplikan dianil selam 96 jam pada suhu 900 °C dalamfumace vakum. Kemudian dilakukan pengukuran difraksi sinar-X clan hasilnya dihaluskan dengan software RIEIAN. Studi strukturmikro dilakukan dengan memakai alat SEM 515 buatanPHll..IPS pada perbesaran 2000 kali clan tegangan 20 keV. Hasil pengamatan tadi memperlihatkan bahwa terjadi perbesarandiameter granular sesuai dengan penambahan kadar unsur La. Pada awal studi ini dapat disimpulkan bahwa sifatmagnetoresistancebahan tergantung pada kerapatan bahan, ukuran granular clan fraksi rasa utama Sml-xLaxM~Ge, Analisis sifat magnetoresistancedengan model magnetic granular solid dapat menjelaskan fenomena proses hamburan yang terkait dengan sifat resistansibahan.